Lithium ion secondary battery, positive electrode active material, and electric device

By using lithium nickel cobalt manganese oxide with high nickel element content and an optimized secondary particle structure, the problem of low circulation performance of the positive electrode material of nickel cobalt manganese ternary material is solved, and the higher circulation performance and stability of lithium-ion secondary batteries are achieved.

CN119833713AActive Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411730371.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-15
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The lithium-ion battery cycling performance of nickel-cobalt-manganese ternary material as a positive electrode material is relatively low.

Method used

Li-nickel-cobalt manganese oxide with a molar content of nickel elements in all transition metal elements is greater than or equal to 85% and less than 100% as the positive electrode active material, and the structural stability and compressive resistance of the positive electrode active material are improved by adjusting the number proportion and crushing force of the radial primary particles in the secondary particles.

Benefits of technology

It improves the circulation performance of lithium-ion secondary batteries, reduces the cracking of the particles of positive electrode active material during cold pressing and circulation, and improves the electrochemical performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833713A_ABST
    Figure CN119833713A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, in particular to a lithium ion secondary battery, a positive electrode active material and electric equipment, and the lithium ion secondary battery comprises the positive electrode active material; the positive electrode active material comprises secondary particles, the secondary particles comprise primary particles, and the primary particles comprise radial primary particles; the secondary particles comprise radial secondary particles, and based on the total number of the primary particles in a single radial secondary particle, the number of the radial primary particles accounts for 60%-100%; the crushing force of the radial secondary particles is 2 mN to 50 mN. The specific capacity of the positive electrode active material is relatively high, the stress accumulation degree is relatively low in the cyclic charge-discharge process, the generated stress is easier to release, and the anti-pressure capability is better, so that the electrochemical performance of the lithium ion secondary battery is improved, and meanwhile, the cycle performance is relatively good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a lithium-ion secondary battery, a battery and an electrical device. Background Art

[0002] In recent years, lithium-ion batteries have made great progress. Lithium-ion batteries can be widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as electric vehicles, power tools, military equipment, aerospace and other fields.

[0003] Among them, when lithium-ion batteries are used in electric bicycles, electric motorcycles, electric cars and other electric vehicle fields, as the market has higher and higher requirements for the endurance of electric vehicles, nickel-cobalt-manganese ternary materials as positive electrode active materials have low cycle performance and need to be further improved. The above statements are only used to provide background technical information related to this application and do not necessarily constitute prior art. Summary of the invention

[0004] In view of this, the main technical problem to be solved by this application is the low cycle performance of batteries using nickel-cobalt-manganese ternary materials as positive electrode materials, thereby providing a lithium-ion secondary battery, a positive electrode active material and electrical equipment that can improve the cycle performance of batteries using nickel-cobalt-manganese ternary materials as positive electrode materials.

[0005] The first aspect of the present application provides a lithium-ion secondary battery, comprising a positive electrode plate, a negative electrode plate and an electrolyte; the positive electrode plate comprises a positive electrode active material, the positive electrode active material comprises lithium nickel cobalt manganese oxide, and the molar content of nickel in all transition metal elements is greater than or equal to 85% and less than 100%; the positive electrode active material comprises secondary particles, the secondary particles comprise primary particles, the primary particles comprise radial primary particles, in the cross-sectional scanning electron microscope image of the secondary particles, the radial primary particles are primary particles in which the minimum angle between the long axis direction of the primary particles and the radius direction of the secondary particles is less than or equal to 20°; the secondary particles comprise radial secondary particles, based on the total number of primary particles in a single radial secondary particle, the number of radial primary particles accounts for 60% to 100%; the crushing force of the radial secondary particles is 2mN to 50mN.

[0006] In this embodiment, the molar content of nickel in all transition metal elements is greater than or equal to 85% and less than 100%. Based on the total number of primary particles in a single radial secondary particle, the number of radial primary particles accounts for 60% to 100%. The radial primary particles with a larger number make the arrangement of primary particles inside the secondary particles more orderly, and the secondary particles tend to be isotropic. During the cyclic charge and discharge process, the primary particles in the secondary particles expand and contract along the (003) crystal plane; the radial primary particles in the radial secondary particles expand or contract in a direction perpendicular to or tending to be perpendicular to the radius, and the stress generation The generation of primary particles will be restricted, the mutual extrusion between primary particles will be reduced, the local stress concentration in the radial secondary particles will be relatively small, and the generated stress will be easier to release, which is beneficial to improving the compressive strength of the positive electrode active material and alleviating the cracking problem of the radial secondary particles, thereby alleviating the cracking problem of the positive electrode active material, and thus is beneficial to improving the cycle performance of lithium-ion secondary batteries; the crushing force of the radial secondary particles is 2mN to 50mN, and the particles have a high compressive strength, which is beneficial to reducing the cracking of the positive electrode active material particles during cold pressing and cycling, thereby helping to improve the electrochemical properties and stability of the positive electrode active material.

[0007] In one embodiment, the average particle size of the primary particles is 50 nm to 2 μm. In the embodiment of the present application, the average particle size of the primary particles is within the above range, so that the stress accumulation degree inside the secondary particles is lower and the generated stress is easier to release.

[0008] In one embodiment, based on the total number of primary particles in a single radial secondary particle, the number of radial primary particles accounts for 75% to 95%. The number of radial primary particles accounts for 75% to 95% of the total number of primary particles in a single radial secondary particle. ...

[0009] In one embodiment, the crushing force of the radial secondary particles is 10 mN to 40 mN. The crushing force of the radial secondary particles within the above range is conducive to further improving the compressive strength of the positive electrode active material and reducing the cracking of the positive electrode active material particles during cold pressing and cycling, thereby further improving the electrochemical performance of the positive electrode active material.

[0010] In one embodiment, the average particle size of the primary particles is 100 nm to 500 nm. In the embodiment of the present application, the average particle size of the primary particles is within the above range, so that the stress accumulation degree inside the secondary particles is lower and the generated stress is easier to release.

[0011] In one embodiment, in the positive electrode active material, based on the total number of secondary particles, the number of radial secondary particles accounts for 75% to 100%. In the embodiment of the present application, the number of radial secondary particles in the secondary particles accounts for a large proportion, and the radial secondary particles have a major impact on the performance of the positive electrode active material. The radial secondary particles can alleviate the problem of secondary particle cracking. The radial secondary particles have better performance, which can effectively improve the overall performance of the positive electrode active material, reduce the probability of cracking of the positive electrode active material during the cycle, and improve the cycle performance of the lithium-ion secondary battery.

[0012] In one embodiment, in the positive electrode active material, based on the total number of secondary particles, the number of radial secondary particles accounts for 85% to 100%. In the embodiment of the present application, the number of radial secondary particles in the secondary particles is further increased, which can further alleviate the secondary particle cracking problem, and can further effectively improve the overall performance of the positive electrode active material, reduce the probability of cracking of the positive electrode active material during the cycle, and improve the cycle performance of the lithium ion secondary battery.

[0013] In one embodiment, in a cross-sectional scanning electron microscope image of the secondary particles, the length of the major axis of the primary particles is 0.3 μm to 3 μm. In the embodiment of the present application, the major axis size of the primary particles is within the above range, and the secondary particles are easy to release stress, so that the stress accumulation degree of the secondary particles is reduced, the structural stability of the secondary particles is increased, and the compressive resistance of the secondary particles is increased, so the crushing force is also increased.

[0014] In one embodiment, in a cross-sectional scanning electron microscope image of the secondary particles, the major axis length of the primary particles is 0.5 μm to 2 μm. In the embodiment of the present application, the major axis size of the primary particles is within the above range, and the secondary particles are easy to release stress, so that the stress accumulation degree of the secondary particles is reduced, the structural stability of the secondary particles is increased, and the compressive resistance of the secondary particles is increased, so the crushing force is also increased.

[0015] In one embodiment, the volume average particle size Dv50 of the positive electrode active material is 6 μm to 15 μm. In the embodiment of the present application, the volume average particle size Dv50 of the positive electrode active material is within the above range, the positive electrode active material has a larger specific surface area, better crushing force, and better electrochemical performance.

[0016] In one embodiment, the volume average particle size Dv50 of the positive electrode active material is 9 μm to 12 μm. In the embodiment of the present application, the volume average particle size Dv50 of the positive electrode active material is within the above range, and the electrochemical performance of the positive electrode active material is better.

[0017] In one embodiment, the volume average particle size Dv2 of the positive electrode active material is 0.5 μm to 4 μm. The larger the Dv2 value, the less the content of the positive electrode active material powder, indicating that the radial primary particles with a larger number can improve the structural stability of the secondary particles, and are not prone to breakage and cracking during processing, and Dv2 remains at a high level.

[0018] In one embodiment, the volume average particle size Dv2 of the positive electrode active material is 0.8 μm to 3 μm. The larger the Dv2 value, the less the content of the positive electrode active material powder, indicating that the radial primary particles with a larger number can improve the structural stability of the secondary particles, and are not prone to breakage and cracking during processing, and Dv2 remains at a high level.

[0019] In one embodiment, the specific surface area of ​​the positive electrode active material is 0.2 m 2 / g~1.0m 2 In the embodiment of the present application, the specific surface area of ​​the positive electrode active material is within the above range, so that the compaction density of the positive electrode active material is better, and the energy density of the lithium ion secondary battery is better.

[0020] In one embodiment, the specific surface area of ​​the positive electrode active material is 0.3 m 2 / g~0.7m 2 In the embodiment of the present application, the specific surface area of ​​the positive electrode active material is within the above range, so that the compaction density of the positive electrode active material is better, and the energy density of the lithium ion secondary battery is better.

[0021] In one embodiment, the cross-sectional porosity of the positive electrode active material is 2% to 8%. In the embodiment of the present application, the cross-sectional porosity of the positive electrode active material is within the above range, so that the positive electrode active material can release stress, alleviate the occurrence of secondary particle cracking of the positive electrode active material, and improve the electrochemical cycle performance of the lithium ion secondary battery.

[0022] In one embodiment, the cross-sectional porosity of the positive electrode active material is 3% to 6%. In the embodiment of the present application, the cross-sectional porosity of the positive electrode active material is within the above range, so that the positive electrode active material can release stress, alleviate the occurrence of secondary particle cracking of the positive electrode active material, and improve the electrochemical cycle performance of the lithium ion secondary battery.

[0023] In one embodiment, the cross-sectional average pore size of the positive electrode active material is 0.1 μm to 2 μm. In the embodiment of the present application, the cross-sectional average pore size of the positive electrode active material is within the above range, so that the positive electrode active material can well relieve stress and release stress, and the compaction density of the positive electrode active material is better, so that the energy density of the lithium ion secondary battery is better.

[0024] In one embodiment, within the pressure range of 0 to 5 T, the change rate of the volume average particle size Dv2 of the positive electrode active material is less than or equal to 20%. In the embodiment of the present application, after the positive electrode active material is pressed, the amount of micropowder particles is at a relatively low level, indicating that the positive electrode active material has a high compressive resistance and a large crushing force.

[0025] In one embodiment, the nickel content of the radial secondary particles from the center to the surface area is equal, or the difference in the nickel content from the center to the surface area is less than or equal to 2%. In the embodiment of the present application, the nickel content in the radial secondary particles is uniform from the center area to the surface area, that is, the nickel element in the radial secondary particles is uniformly distributed, so that the electrochemical performance of the positive electrode active material is better.

[0026] In one embodiment, the manganese content of the radial secondary particles from the center to the surface area is equal, or the difference in the manganese content from the center to the surface area is less than or equal to 0.5%. In the embodiment of the present application, the manganese content in the radial secondary particles is uniform from the center area to the surface area, that is, the manganese element in the radial secondary particles is uniformly distributed, so that the electrochemical performance of the positive electrode active material is better.

[0027] In one embodiment, the positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 e O f The material, wherein the M1 element includes one or more of Zr, Ti, Y, Sb, W, Mo, Ba, Ta, Nb, and Al, 0.9≤a≤1.2, 0.85≤b<1, 0.01≤c≤0.09, 0.01≤d≤0.05, 0.001≤e≤0.005, 1.6≤f≤2.4, and b+c+d+e=1. The positive electrode active material provided in this embodiment combines the advantages of the three elements of nickel, cobalt, and manganese. At the same time, the doping element M1 helps to improve the bulk stability and electrical stability of the positive electrode active material, reduce the cation mixing problem caused by high nickel, and is conducive to promoting the growth of radial primary particles, thereby improving the electrochemical properties of the positive electrode active material.

[0028] In one embodiment, 0.9≤b<1, and / or, 0.002≤e≤0.004. In the embodiment of the present application, in the lithium nickel cobalt manganese oxide, the molar content of nickel in all transition metal elements is greater than or equal to 0.9, which is conducive to further improving the energy density of the positive electrode active material; the doping elements are within the above range, which can further improve the electrochemical performance of the lithium nickel cobalt manganese oxide.

[0029] In one embodiment, the positive electrode active material further includes a coating layer, the coating layer is located on the structure formula Li a Ni b Co c Mn d M1 e O f The coating layer includes Co and / or B elements on the surface of the material. In the embodiment of the present application, Co can repair the grain boundary, improve the Young's modulus of the secondary particles, enhance the electrochemical stability of the surface of the secondary particles, and improve the cycle life; B can refine the primary grains, improve the ability of lithium ions to be deintercalated on the surface, and improve the electrochemical performance of the lithium ion secondary battery.

[0030] The second aspect of the present application also provides a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, the molar content of nickel in all transition metal elements is greater than or equal to 85% and less than 100%; the positive electrode active material includes secondary particles, the secondary particles include primary particles, the primary particles include radial primary particles, in the cross-sectional scanning electron microscope image of the secondary particles, the radial primary particles are primary particles in which the minimum angle between the long axis direction of the primary particles and the radius direction of the secondary particles is less than or equal to 20°; the secondary particles include radial secondary particles, based on the total number of primary particles in a single radial secondary particle, the number of radial primary particles accounts for 60% to 100%; the crushing force of the radial secondary particles is 2mN to 50mN. In this embodiment, based on the total number of primary particles in a single radial secondary particle, the number of radial primary particles accounts for 60% to 100%. The radial primary particles with a larger number account for a higher order of arrangement of primary particles inside the secondary particles, and the secondary particles tend to be isotropic. During the cyclic charge and discharge process, the primary particles in the secondary particles expand and contract along the (003) crystal plane; the radial primary particles in the radial secondary particles expand or contract along a direction perpendicular or tending to be perpendicular to the radius, the stress generation will be limited, the mutual extrusion between the primary particles is reduced, the local stress concentration in the radial secondary particles is relatively small, and the generated stress is easier to release, which is beneficial to improving the compressive strength of the positive electrode active material and alleviating the cracking problem of the radial secondary particles, thereby alleviating the cracking problem of the positive electrode active material, and thus is beneficial to improving the cycle performance of the lithium-ion secondary battery; the crushing force of the radial secondary particles is 2mN to 50mN, and the particles have a high compressive strength, which is beneficial to reducing the cracking of the positive electrode active material particles during cold pressing and cycling, thereby helping to improve the electrochemical properties and stability of the positive electrode active material.

[0031] The third aspect of the present application also provides an electrical device, comprising the lithium ion battery of the first aspect of the present application and / or the positive electrode active material of the second aspect of the present application. Since the electrical device of the present application comprises the lithium ion battery and / or the positive electrode active material provided by the present application, it has at least the same advantages as the lithium ion battery.

[0032] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a cross-sectional scanning electron microscope (SEM) photograph of the secondary particles provided in Example 1 of the present application;

[0034] Figure 2 is a schematic diagram of the structure of a battery cell provided in some embodiments of the present application;

[0035] Figure 3 is a schematic diagram of the exploded structure of a lithium-ion secondary battery provided in some embodiments of the present application;

[0036] Figure 4 It is a schematic diagram of an electrical device according to one embodiment of the present application. DETAILED DESCRIPTION

[0037] Hereinafter, the embodiments of the lithium-ion secondary battery, battery and electrical equipment of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0038] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0039] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0040] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0041] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0042] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.

[0043] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0044] During the charge and discharge process of lithium-ion secondary batteries, active lithium ions are embedded and extracted in the positive electrode material, which causes the expansion and contraction of the lattice, thereby generating stress accumulation inside the material particles. This stress accumulation may lead to the formation of microcracks inside the material particles and material breakage, thus affecting the cycle stability and safety of the battery.

[0045] Based on this, the present application proposes a lithium-ion secondary battery, which includes a positive electrode plate, a negative electrode plate and an electrolyte; the positive electrode plate includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel in all transition metal elements is greater than or equal to 85% and less than 100%; the positive electrode active material includes secondary particles, the secondary particles include primary particles, the primary particles include radial primary particles, and in the cross-sectional scanning electron microscope image of the secondary particles, the radial primary particles are primary particles whose minimum angle between the long axis direction of the primary particles and the radius direction of the secondary particles is less than or equal to 20°; the secondary particles include radial secondary particles, and based on the total number of primary particles in a single radial secondary particle, the number of radial primary particles accounts for 60% to 100%; the crushing force of the radial secondary particles is 2mN to 50mN.

[0046] Among them, primary particles refer to single fine grains, which are the most basic units in positive electrode active materials, while secondary particles refer to larger particles formed by the aggregation of multiple primary particles.

[0047] A radial primary particle is a special type of primary particle. The minimum angle between the long axis direction of the primary particle and the radius direction of the secondary particle is less than or equal to 20°. The primary particle is a radial primary particle.

[0048] Radial secondary particles are a special type of secondary particles. The number of radial primary particles in the secondary particles accounts for 60% to 100% of the total number of primary particles in the secondary particles. The secondary particles are radial secondary particles.

[0049] See also Figure 1 , Figure 1 This is a cross-sectional scanning electron microscope (SEM) photograph of the secondary particles provided in Example 1 of the present application. Figure 1 The round particles in the center are secondary particles, which contain many tiny primary particles. Figure 1CD is the radial direction of the secondary particle, AB is the long axis direction of a radial primary particle, and the angle between AB and CD is less than 20°. Figure 1 In the secondary particles shown, the number of radial primary particles accounts for 89% of the total number of primary particles. At this time, the secondary particles are radial secondary particles.

[0050] In the embodiment of the present application, the positive electrode active material of the lithium ion battery includes lithium nickel cobalt manganese oxide. Lithium nickel cobalt manganese oxide gathers the advantages of the three elements of nickel (Ni), cobalt (Co), and manganese (Mn) through the synergistic effect of elements, while maintaining the electrode material with high specific capacity and good stability, it also reduces the preparation cost. Among them, the molar content of nickel element in all transition metal elements is greater than or equal to 85% and less than 100%, which can effectively improve the specific capacity of the positive electrode active material, thereby helping to improve the energy density of the lithium ion battery. The molar proportion of nickel element can be 85%, 88%, 90%, 95%, 99%, etc., or a range composed of any two of the above values, for example, it can be 85% to 88%, 85% to 90%, 90% to 95%, 95% to 99%, etc.

[0051] In the embodiment of the present application, the positive electrode active material includes secondary particles, the secondary particles include primary particles, the primary particles include radial primary particles, and based on the total number of primary particles in a single radial secondary particle, the number of radial primary particles accounts for 60% to 100%. In other words, when the number of radial primary particles in the secondary particles accounts for 60% to 100%, most of the secondary particles are radial primary particles, and the secondary particles are radial secondary particles. The radial primary particles with a large number of primary particles make the arrangement of primary particles inside the secondary particles more orderly, and the secondary particles tend to be isotropic. During the cyclic charge and discharge process, the primary particles in the secondary particles expand and contract along the (003) crystal plane; the radial primary particles in the radial secondary particles expand or contract along the direction perpendicular to or tending to be perpendicular to the radius, and the stress generation will be limited, the mutual extrusion between the primary particles is reduced, and the local stress concentration in the radial secondary particles is relatively small, and the generated stress is easier to release, which is conducive to improving the compressive strength of the positive electrode active material, alleviating the cracking problem of radial secondary particles, thereby alleviating the cracking problem of the positive electrode active material, and thus helping to improve the cycle performance of lithium-ion secondary batteries.

[0052] In the embodiment of the present application, the secondary particles may all be radial secondary particles, or the secondary particles may include radial secondary particles and non-radial secondary particles. Among the non-radial secondary particles, the number of radial primary particles accounts for less than 60%.

[0053] In the embodiment of the present application, the crushing force of the radial secondary particles is 2mN to 50mN. Meeting the above crushing force range, the particles have a high compression resistance, which is beneficial to reducing the cracking of the positive electrode active material particles during cold pressing and cycling, thereby improving the electrochemical performance and stability of the positive electrode active material.

[0054] The radial direction of the secondary particle is specifically the radial direction connecting the farthest point of the primary particle close to the geometric center of the cross section of the secondary particle and the geometric center. In the cross section of the primary particle, the first direction along the geometric center of the cross section of the primary particle has the largest dimension, and the first direction is the long axis direction of the primary particle. The minimum angle is the angle between the above radial direction and the long axis direction of the primary particle. Please refer to Figure 1 , Figure 1 This is a cross-sectional scanning electron microscope (SEM) photograph of the secondary particles provided in Example 1 of the present application. Figure 1 An example of the minimum angle between the major axis direction AB of the primary particle and the radial direction CD of the secondary particle in a cross-sectional scanning electron microscope image of the secondary particle is given in FIG. Figure 1 It is shown that when the minimum angle is less than or equal to 20°, the primary particles are generally arranged radially with the geometric center of the secondary particle cross section as the origin. The minimum angle can be 0°, 5°, 6.8°, 8°, 10°, 13°, 15°, 19°, 20°, etc., or a range consisting of any two of the above values, for example, 0° to 5°, 6.8° to 10°, 13° to 15°, 19° to 20°, etc.

[0055] Wherein, based on the total number of primary particles in a single radial secondary particle, the number of radial primary particles accounts for 60% to 100%. It can be 60%, 65%, 70%, 76%, 80%, 85%, 90%, 99%, 100%, etc., or a range consisting of any two of the above values, for example, it can be 60% to 65%, 70% to 76%, 80% to 85%, 90% to 100%, etc.

[0056] The crushing force of radial secondary particles is 2mN to 50mN. It can be 2mN, 3mN, 6mN, 10mN, 15mN, 22mN, 26mN, 30mN, 40mN, 45mN, 50mN, etc., or a range consisting of any two of the above values, for example, it can be 2mN to 6mN, 10mN to 15mN, 22mN to 26mN, 30mN to 40mN, 45mN to 50mN, etc. The crushing force refers to the maximum pressure that a material can withstand before it breaks under certain conditions. The greater the crushing force, the better the material's compressive resistance.

[0057] The crushing force of radial secondary particles is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.

[0058] In one embodiment, the average particle size of the primary particles is 50 nm to 2 μm.

[0059] Among them, the average particle size of the primary particles is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art. The average particle size of the primary particles is 50nm to 2μm, and can be 50nm, 60nm, 80nm, 1μm, 1.2μm, 1.5μm, 1.6μm, 1.85μm, 2μm, etc., or a range consisting of any two of the above values, for example, it can be 50nm to 60nm, 80nm to 1μm, 1.2μm to 1.6μm, 1.85μm to 2μm, etc. In the embodiment of the present application, the average particle size of the primary particles is in the above range, so that the stress accumulation degree inside the secondary particles is lower, and the generated stress is easier to release.

[0060] In one embodiment, based on the total number of primary particles in a single radial secondary particle, the number of radial primary particles accounts for 75% to 95%, which can be 75%, 76%, 80%, 85%, 90%, 95%, etc., or a range consisting of any two of the above values, for example, 75% to 76%, 80% to 85%, 90% to 95%, etc.

[0061] The proportion of radial primary particles within the above range is conducive to further alleviating stress accumulation during the cyclic charge and discharge process, making it easier to release the stress generated inside the particles, thereby further improving the particle strength of the positive electrode active material and alleviating the problem of particle cracking, and therefore is conducive to further improving the cycle performance of lithium-ion secondary batteries.

[0062] In one embodiment, the Young's modulus of the radial secondary particles is 10mN to 40mN, and may be 10mN, 15mN, 18mN, 22mN, 25mN, 30mN, 36mN, 40mN, etc., or a range consisting of any two of the above values, for example, 10mN to 15mN, 18mN to 22mN, 25mN to 30mN, 36mN to 40mN, etc.

[0063] The crushing force of the radial secondary particles is within the above range, which is beneficial to further improve the compressive strength of the positive electrode active material and reduce the cracking of the positive electrode active material particles during cold pressing and cycling, thereby further improving the electrochemical properties of the positive electrode active material.

[0064] In one embodiment, the average particle size of the primary particles is 100 nm to 500 nm, and may be 100 nm, 110 nm, 150 nm, 165 nm, 200 nm, 230 nm, 250 nm, 275 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, etc., or a range consisting of any two of the above values, for example, 100 nm to 150 nm, 165 nm to 200 nm, 230 nm to 250 nm, 275 nm to 350 nm, 400 nm to 500 nm, etc.

[0065] In the embodiment of the present application, the average particle size of the primary particles is within the above range, so that the stress accumulation degree inside the secondary particles is lower and the generated stress is easier to release.

[0066] In one embodiment, in the positive electrode active material, based on the total number of secondary particles, the number of radial secondary particles accounts for 75% to 100%, which can be 75%, 80%, 85%, 88%, 90%, 96%, 100%, etc., or a range consisting of any two of the above values, for example, 75% to 80%, 80% to 85%, 88% to 90%, 96% to 100%, etc.

[0067] In the embodiment of the present application, the number of radial secondary particles in the secondary particles accounts for a large proportion, and the radial secondary particles have a major influence on the performance of the positive electrode active material. The radial secondary particles can alleviate the problem of secondary particle cracking. The radial secondary particles have better performance, which can effectively improve the overall performance of the positive electrode active material, reduce the probability of cracking of the positive electrode active material during the cycle, and improve the cycle performance of the lithium-ion secondary battery. The number of non-radial secondary particles in the secondary particles accounts for less than 25%, which has little effect on the positive electrode active material.

[0068] In one embodiment, in the positive electrode active material, based on the total number of secondary particles, the number of radial secondary particles accounts for 85% to 100%, which can be 85%, 90%, 92%, 95%, 98%, 99.5%, 100%, etc., or a range consisting of any two of the above values, for example, 85% to 90%, 90% to 92%, 95% to 98%, 99.5% to 100%, etc.

[0069] In the embodiment of the present application, the proportion of radial secondary particles in the secondary particles is further increased, which can further alleviate the cracking problem of secondary particles, can further effectively improve the overall performance of the positive electrode active material, reduce the probability of cracking of the positive electrode active material during the cycle process, and improve the cycle performance of lithium-ion secondary batteries.

[0070] In one embodiment, in a cross-sectional scanning electron microscope image of the secondary particle, the major axis length of the primary particle is 0.3 μm to 3 μm, and may be 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.3 μm, 2 μm, 2.2 μm, 2.6 μm, 3 μm, etc., or a range of any two of the above values, for example, 0.3 μm to 1 μm, 1 μm to 2.2 μm, 2.2 μm to 3 μm, etc.

[0071] Among them, the first direction along the geometric center of the cross section of the primary particle has a maximum size, and the maximum size is the length of the major axis of the primary particle. In the embodiment of the present application, the major axis size of the primary particle is within the above range, and the secondary particle is easy to release stress, so that the stress accumulation degree of the secondary particle is reduced, the structural stability of the secondary particle is increased, and the compressive resistance of the secondary particle is increased, so the crushing force is also improved.

[0072] In one embodiment, in a cross-sectional scanning electron microscope image of the secondary particle, the major axis length of the primary particle is 0.5 μm to 2 μm, and may be 0.5 μm, 0.8 μm, 1 μm, 1.3 μm, 2 μm, etc., or a range of any two of the above values, for example, 0.5 μm to 0.8 μm, 1 μm to 1.3 μm, 1.3 μm to 2 μm, etc.

[0073] In the embodiment of the present application, the major axis length of the primary particles is within the above range, and the secondary particles are easy to release stress, so that the stress accumulation degree of the secondary particles is reduced, the structural stability of the secondary particles is increased, the compressive resistance of the secondary particles is increased, and thus the crushing force is also increased.

[0074] In one embodiment, the volume average particle size Dv50 of the positive electrode active material is 6 μm to 15 μm. Dv50 refers to the particle size corresponding to 50% of the volume distribution. Dv50 can be 6 μm, 9 μm, 10 μm, 13 μm, 15 μm, etc., or a range value composed of any two of the above values, for example, 6 μm to 10 μm, 10 μm to 13 μm, 13 μm to 15 μm, etc. The volume average particle size Dv50 is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.

[0075] In the embodiment of the present application, the volume average particle size Dv50 of the positive electrode active material is within the above range, the positive electrode active material has a larger specific surface area, better crushing force, and better electrochemical performance of the positive electrode active material.

[0076] In one embodiment, the volume average particle size Dv50 of the positive electrode active material is 9 μm to 12 μm, and may be 9 μm, 10 μm, 11 μm, 12 μm, etc., or a range of any two of the above values, for example, 9 μm to 10 μm, 10 μm to 11 μm, 11 μm to 12 μm, etc.

[0077] In the embodiment of the present application, the volume average particle size Dv50 of the positive electrode active material is within the above range, and the electrochemical performance of the positive electrode active material is better.

[0078] In one embodiment, the volume average particle size Dv2 of the positive electrode active material is 0.5μm to 4μm. Dv2 refers to the particle size corresponding to 2% in the volume distribution. Dv2 can be 0.5μm, 1μm, 2μm, 3μm, 4μm, etc., or a range value composed of any two of the above values, for example, 0.5μm to 1μm, 1μm to 2μm, 2μm to 3μm, 3μm to 4μm, etc. The volume average particle size Dv2 is common knowledge in the art and has a meaning known in the art, and can be measured by methods and instruments in the art. In the embodiment of the present application, the Dv2 value is large, and the content of the micropowder of the positive electrode active material is small, indicating that the radial primary particles with a large number can improve the structural stability of the secondary particles, and are not prone to breakage and cracking during processing, and Dv2 remains at a high level.

[0079] In one embodiment, the volume average particle size Dv2 of the positive electrode active material is 0.8 μm to 3 μm. It can be 0.8 μm, 1 μm, 2 μm, 3 μm, etc., or a range value composed of any two of the above values, for example, 0.8 μm to 1 μm, 1 μm to 2 μm, 2 μm to 3 μm, etc. The larger the Dv2 value, the less the content of the micro powder of the positive electrode active material, indicating that the radial primary particles with a larger number can improve the structural stability of the secondary particles, and are not prone to breakage and cracking during processing, and Dv2 remains at a high level.

[0080] In one embodiment, the specific surface area of ​​the positive electrode active material is 0.2 m 2 / g~1.0m 2 / g. It can be 0.2m 2 / g, 0.4m 2 / g, 0.55m 2 / g, 0.8m 2 / g, 1.0m 2 / g, etc., or a range consisting of any two of the above values, for example, 0.2m 2 / g~0.4m 2 / g, 0.55m 2 / g~0.8m 2 / g, 0.8m 2 / g~1.0m 2 / g, etc. The specific surface area is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.

[0081] In the embodiment of the present application, the specific surface area of ​​the positive electrode active material is within the above range, so that the compaction density of the positive electrode active material is better, and the energy density of the lithium ion secondary battery is better.

[0082] In one embodiment, the specific surface area of ​​the positive electrode active material is 0.3 m 2 / g~0.7m 2 / g. It can be 0.3m 2 / g, 0.4m 2 / g, 0.55m 2 / g, 0.62m 2 / g, 0.7m 2 / g, etc., or a range consisting of any two of the above values, for example, 0.3m 2 / g~0.4m 2 / g, 0.55m 2 / g~0.62m 2 / g, 0.62m 2 / g~0.7m 2 In the embodiment of the present application, the specific surface area of ​​the positive electrode active material is within the above range, so that the compaction density of the positive electrode active material is better, and the energy density of the lithium ion secondary battery is better.

[0083] In one embodiment, the cross-sectional porosity of the positive electrode active material is 2% to 8%. It can be 2%, 4%, 5%, 6%, 8%, etc., or a range of any two of the above values, for example, 2% to 4%, 4% to 6%, 6% to 8%, etc. Among them, the cross-sectional porosity is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.

[0084] The cross-sectional porosity of the positive electrode active material refers to the proportion of space occupied by the gaps between particles. In the positive electrode material of a lithium-ion battery, the porosity has a significant effect on the performance of the battery. In the embodiment of the present application, the cross-sectional porosity of the positive electrode active material is within the above range, so that the positive electrode active material can release stress, alleviate the occurrence of secondary particle cracking of the positive electrode active material, and improve the electrochemical cycle performance of the lithium-ion secondary battery.

[0085] In one embodiment, the cross-sectional porosity of the positive electrode active material is 3% to 6%, and may be 3%, 4%, 5%, 5.5%, 6%, etc., or a range of any two of the above values, for example, 3% to 4%, 4% to 6%, 5.5% to 6%, etc.

[0086] In the embodiment of the present application, the cross-sectional porosity of the positive electrode active material is within the above range, so that the positive electrode active material can release stress, alleviate the occurrence of secondary particle cracking of the positive electrode active material, and improve the electrochemical cycle performance of the lithium ion secondary battery.

[0087] In one embodiment, the cross-sectional average pore size of the positive electrode active material is 0.1 μm to 2 μm. It can be 0.1 μm, 0.8 μm, 1 μm, 1.3 μm, 2 μm, etc., or a range value composed of any two of the above values, for example, 0.1 μm to 0.8 μm, 0.8 μm to 1.3 μm, 1.3 μm to 2 μm, etc. Among them, the cross-sectional average pore size is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.

[0088] The cross-sectional average pore diameter refers to the average value of the diameter of the pores in the positive electrode active material. In the embodiment of the present application, the cross-sectional average pore diameter of the positive electrode active material is within the above range, so that the positive electrode active material can well relieve stress and release stress, and the compaction density of the positive electrode active material is better, so that the energy density of the lithium-ion secondary battery is better.

[0089] In one embodiment, within the pressure range of 0 to 5 T, the change rate of the volume average particle size Dv2 of the positive electrode active material is less than or equal to 20%. It can be 2%, 5%, 8%, 10%, 15%, 20%, etc., or a range value composed of any two of the above values, for example, 2% to 5%, 8% to 15%, 15% to 20%, etc.

[0090] In the embodiment of the present application, after the positive electrode active material is pressed, the amount of micro powder particles is at a relatively low level, indicating that the positive electrode active material has a strong compressive resistance and a large crushing force.

[0091] In one embodiment, the nickel content of the radial secondary particles from the center to the surface area is equal, or the difference in the nickel content from the center to the surface area is less than or equal to 2%. In the embodiment of the present application, the nickel content in the radial secondary particles is uniform from the center area to the surface area, that is, the nickel element in the radial secondary particles is uniformly distributed. The uniform distribution of nickel elements can reduce material defects and uneven distribution of nickel element concentration in local areas, and promote Li + The smooth deintercalation and deintercalation and better utilization of the material's capacity; at the same time, the uniform distribution of nickel elements alleviates the unevenness of the material's deintercalation and deintercalation of lithium, can reduce local differences, improve the material's cycle stability, and make the positive electrode active material have better electrochemical performance. In other embodiments, the difference in the content of nickel elements from the center to the surface area can also be less than or equal to 1.8%.

[0092] In the implementation manner of the present application, the content of nickel element refers to the mass proportion of nickel element in all elements in the test area.

[0093] In one embodiment, the manganese content of the radial secondary particles from the center to the surface area is equal, or the difference in the manganese content from the center to the surface area is less than or equal to 0.5%. In the embodiment of the present application, the manganese content in the radial secondary particles is uniform from the center area to the surface area, that is, the manganese in the radial secondary particles is uniformly distributed. The uniform distribution of manganese reduces material defects and uneven distribution of manganese concentration in local areas, and promotes Li + The smooth deintercalation and deintercalation and better utilization of the material's capacity; at the same time, the uniform distribution of manganese elements alleviates the unevenness of the material's deintercalation and deintercalation of lithium, can reduce local differences, improve the material's cycle stability, and make the positive electrode active material have better electrochemical performance. In other embodiments, the difference in the content of manganese elements from the center to the surface area can also be less than or equal to 0.4%. In other embodiments, the difference in the content of manganese elements from the center to the surface area can also be the same as the difference in the content of nickel elements from the center to the surface area.

[0094] In the implementation manner of the present application, the content of manganese refers to the mass proportion of manganese in all elements in the test area.

[0095] In one embodiment, the positive electrode active material does not include a coating layer, and the content of cobalt in the radial secondary particles from the center to the surface area is equal, or the difference in the content of cobalt from the center to the surface area is less than or equal to 0.6%. In the embodiment of the present application, the content of cobalt in the radial secondary particles is uniform from the center area to the surface area, that is, the cobalt in the radial secondary particles is uniformly distributed. The uniform distribution of cobalt reduces material defects and uneven distribution of cobalt concentration in local areas, and promotes Li + The deintercalation and extraction are carried out smoothly and the capacity of the material is better utilized; at the same time, the uniform distribution of the cobalt element alleviates the unevenness of the material's deintercalation and extraction of lithium, can reduce local differences, improve the material's cycle stability, and make the electrochemical performance of the positive electrode active material better. In other embodiments, the difference in the content of the cobalt element from the center to the surface area can also be less than or equal to 0.5%. In other embodiments, the difference in the content of the cobalt element from the center to the surface area can also be the same as the difference in the content of the nickel element from the center to the surface area or the difference in the content of the manganese element from the center to the surface area.

[0096] In the implementation manner of the present application, the content of cobalt element refers to the mass proportion of cobalt element in all elements in the test area.

[0097] In one embodiment, the positive electrode active material includes a structural formula of Li a Nib Co c Mn d M1 e O f material, wherein the M1 element includes one or more of Zr, Ti, Y, Sb, W, Mo, Ba, Ta, Nb, and Al, 0.9≤a≤1.2, 0.85≤b<1, 0.01≤c≤0.09, 0.01≤d≤0.05, 0.001≤e≤0.005, 1.6≤f≤2.4, and b+c+d+e=1.

[0098] Among them, lithium (Li) element provides lithium ions, which move between the positive and negative electrodes when the battery is charged and discharged, and are the key to battery energy storage and release. Nickel (Ni) element helps to improve the energy density of the positive electrode active material. In the above embodiment, nickel (Ni) element accounts for a high proportion of other metal elements except lithium element, so the positive electrode active material has a higher energy density. Cobalt (Co) element helps to stabilize the material structure, reduce impedance value, increase conductivity, and improve cycle and efficiency performance. Manganese (Mn) element can reduce material cost and improve the safety and stability of the material.

[0099] The doping element M1 helps to improve the bulk stability and electrical stability of the positive electrode active material, reduce the cation mixing problem caused by high nickel, and promote the growth of radial primary particles, thereby improving the electrochemical performance of the positive electrode active material.

[0100] In one embodiment, 0.9≤b<1, and / or, 0.002≤e≤0.004. In the embodiment of the present application, in the lithium nickel cobalt manganese oxide, the molar content of nickel in all transition metal elements is greater than or equal to 0.9, which is conducive to further improving the energy density of the positive electrode active material; the doping elements are within the above range, which can further improve the electrochemical performance of the lithium nickel cobalt manganese oxide.

[0101] In one embodiment, the positive electrode active material further includes a coating layer, the coating layer is located on the structure formula Li a Ni b Co c Mn d M1 e O f The coating layer comprises Co element and / or B element on the surface of the material.

[0102] In the implementation mode of the present application, by a Ni b Co c Mn d M1 e O fThe surface of the material is coated with a substance containing the Co element. The Co element can penetrate into the grain boundary of the primary particles, repair the grain boundary, increase the Young's modulus of the secondary particles, enhance the electrochemical stability of the secondary particle surface, and improve the cycle life. The coating layer contains the B element, which can refine the primary grains, improve the ability of lithium ions to be deintercalated on the surface, and improve the electrochemical performance of lithium-ion secondary batteries.

[0103] The present application also provides a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, the molar content of nickel in all transition metal elements is greater than or equal to 85% and less than 100%; the positive electrode active material includes secondary particles, the secondary particles include primary particles, the primary particles include radial primary particles, in the cross-sectional scanning electron microscope image of the secondary particles, the radial primary particles are primary particles in which the minimum angle between the long axis direction of the primary particles and the radius direction of the secondary particles is less than or equal to 20°; the secondary particles include radial secondary particles, based on the total number of primary particles in a single radial secondary particle, the number of radial primary particles accounts for 60% to 100%; the crushing force of the radial secondary particles is 2mN to 50mN.

[0104] In the embodiment of the present application, the molar content of nickel in all transition metal elements is greater than or equal to 85% and less than 100%, which can effectively improve the specific capacity of the positive electrode active material, thereby facilitating the improvement of the energy density of the lithium-ion battery; in the embodiment of the present application, based on the total number of primary particles in a single radial secondary particle, the number of radial primary particles accounts for 60% to 100%, and the radial primary particles with a larger number make the arrangement of primary particles inside the secondary particles more orderly, and the secondary particles tend to be isotropic. During the cyclic charge and discharge process, the primary particles in the secondary particles expand and contract along the (003) crystal plane; the radial primary particles in the radial secondary particles are arranged perpendicularly or tending to be perpendicular to the semi-circular surface. The radial direction of the secondary particles expands or contracts, the stress generation will be limited, the mutual extrusion between the primary particles is reduced, the local stress concentration in the radial secondary particles is relatively small, and the generated stress is easier to release, which is beneficial to improving the compressive strength of the positive electrode active material and alleviating the cracking problem of the radial secondary particles, thereby alleviating the cracking problem of the positive electrode active material, and thus is beneficial to improving the cycle performance of the lithium-ion secondary battery; in the embodiment of the present application, the crushing force of the radial secondary particles is 2mN~50mN, and the crushing force of the radial secondary particles is relatively large, which is beneficial to improving the compressive strength of the positive electrode active material and reducing the cracking of the positive electrode active material particles during cold pressing and cycling, thereby being beneficial to improving the electrochemical properties of the positive electrode active material.

[0105] The present application also provides an electrical device, comprising the above-mentioned lithium ion secondary battery and / or positive electrode active material, which has the advantages that the lithium ion secondary battery and / or the positive electrode active material are the same or similar.

[0106] In addition, the lithium ion secondary battery, battery cell, and electric equipment of the present application will be described below with reference to the drawings as appropriate.

[0107] In the embodiments of the present application, a battery cell refers to the smallest unit that makes up a battery. A battery cell also includes an electrolyte and a separator. The separator is disposed between the positive electrode and the negative electrode, and mainly prevents the positive and negative electrodes from short-circuiting, while allowing ions to pass through. During the battery charge and discharge process, the active ion Li+ is embedded and removed back and forth between the positive electrode and the negative electrode, and the electrolyte plays the role of conducting ions between the positive electrode and the negative electrode.

[0108] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material of the above embodiment of the present application.

[0109] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0110] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0111] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0112] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0113] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0114] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes the negative electrode active material of the above embodiment.

[0115] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0116] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0117] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0118] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0119] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)).

[0120] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0121] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.

[0122] In some embodiments, the electrolyte includes an electrolyte salt and a solvent.

[0123] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0124] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0125] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0126] In some embodiments, the lithium-ion secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0127] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0128] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be made into a battery cell assembly by a winding process or a lamination process.

[0129] In some embodiments, Figure 2 As shown, the battery cell 10 may include an outer package. The outer package may be used to encapsulate the battery cell assembly 11 and the electrolyte. The outer package includes an end cap 12, a housing 13 and other functional components.

[0130] The end cap 12 refers to a component that covers the opening of the shell 13 to isolate the internal environment of the battery cell 10 from the external environment. Without limitation, the shape of the end cap 12 can be adapted to the shape of the shell 13 to match the shell 13. Optionally, the end cap 12 can be made of a material with a certain hardness and strength (such as aluminum alloy), so that the end cap 12 is not easily deformed when squeezed and collided, so that the battery cell 10 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals 12a can be provided on the end cap 12. The electrode terminal 12a can be used to electrically connect to the battery cell assembly 11 for outputting or inputting electrical energy of the battery cell 10. In some embodiments, the end cap 12 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 10 reaches a threshold. The material of the end cap 12 can also be a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not impose special restrictions on this. In some embodiments, an insulating member (not shown) may be provided inside the end cap 12 to isolate the electrical connection components in the housing 13 from the end cap 12 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.

[0131] The shell 13 is a component used to cooperate with the end cap 12 to form the internal environment of the battery cell 10, wherein the formed internal environment can be used to accommodate the battery cell assembly 11, electrolyte and other components. The shell 13 and the end cap 12 can be independent components, and an opening can be set on the shell 13, and the internal environment of the battery cell 10 is formed by covering the opening with the end cap 12 at the opening. Without limitation, the end cap 12 and the shell 13 can also be integrated. Specifically, the end cap 12 and the shell 13 can form a common connection surface before other components are put into the shell, and when the interior of the shell 13 needs to be encapsulated, the end cap 12 covers the shell 13. The shell 13 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 13 can be determined according to the specific shape and size of the battery cell assembly 11. The material of the shell 13 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.

[0132] The housing 13 may contain one or more battery cell assemblies 11. The portions of the positive and negative electrodes that do not contain active materials each constitute a tab 11a. The positive tab and the negative tab may be located at one end of the main body or at both ends of the main body. During the charge and discharge process of the battery, the positive active material and the negative active material react with the electrolyte, and the tab 11a connects the electrode terminal to form a current loop.

[0133] Please refer to Figure 3 , Figure 3Schematic diagram of the exploded structure of a lithium-ion secondary battery provided for some embodiments of the present application. The lithium-ion secondary battery 100 includes a box 20 and a battery cell 10, and the battery cell 10 is contained in the box 20. Among them, the box 20 is used to provide a storage space for the battery cell 10, and the box 20 can adopt a variety of structures. In some embodiments, the box 20 may include a first part 21 and a second part 22, the first part 21 and the second part 22 cover each other, and the first part 21 and the second part 22 jointly define a storage space for accommodating the battery cell 10. The second part 22 may be a hollow structure with one end open, the first part 21 may be a plate-like structure, and the first part 21 covers the open side of the second part 22, so that the first part 21 and the second part 22 jointly define a storage space; the first part 21 and the second part 22 may also be hollow structures with one side open, and the open side of the first part 21 covers the open side of the second part 22. Of course, the box 20 formed by the first part 21 and the second part 22 may be in a variety of shapes, such as a cylinder, a cuboid, etc.

[0134] In the lithium-ion secondary battery 100, there may be multiple battery cells 10, and the multiple battery cells 10 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 10 are both connected in series and in parallel. The multiple battery cells 10 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 10 is accommodated in the box 20; of course, the lithium-ion secondary battery 100 may also be a battery module formed by connecting multiple battery cells 10 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 20. The lithium-ion secondary battery 100 may also include other structures, for example, the lithium-ion secondary battery 100 may also include a busbar component for realizing electrical connection between the multiple battery cells 10.

[0135] The battery cell 10 may be cylindrical, flat, rectangular or in other shapes.

[0136] In some embodiments, the lithium-ion secondary battery 100 can be assembled into a battery module. The number of batteries contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0137] In addition, the present application also provides an electrical device, which includes at least one of the lithium-ion secondary batteries and / or battery cells provided in the present application. The lithium-ion secondary battery or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0138] As the electrical equipment, a lithium-ion secondary battery and / or a battery can be selected according to its usage requirements.

[0139] Figure 4 As shown, it is an electric device as an example. The electric device is a vehicle such as a pure electric vehicle, a hybrid electric vehicle or a plug-in hybrid electric vehicle. A structural schematic diagram of a vehicle 1000 is specifically provided. A lithium-ion secondary battery 100 is arranged inside the vehicle 1000, and the lithium-ion secondary battery 100 can be arranged at the bottom, head or tail of the vehicle 1000. The lithium-ion secondary battery 100 can be used to power the vehicle 1000. For example, the lithium-ion secondary battery 100 can be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300. The controller 200 is used to control the lithium-ion secondary battery 100 to power the motor 300, for example, for the working power demand of the vehicle 1000 during starting, navigation and driving.

[0140] In some embodiments of the present application, the lithium-ion secondary battery 100 can be used not only as an operating power source for the vehicle 1000, but also as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.

[0141] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0142] Example 1

[0143] Preparation method of positive electrode active material:

[0144] S1: Prepare the high nickel ternary material substrate precursor by coprecipitation reaction: According to the molar ratio of Ni, Co and Mn elements in the high nickel ternary material substrate of 0.918:0.07:0.01, prepare the Ni, Co, Mn sulfate solution with a concentration of 5 mol / L, and prepare the NaOH solution with a concentration of 10 mol / L and the ammonia solution with a concentration of 12 mol / L at the same time, add 20% of pure water by volume to the reactor, pump the above three solutions into the reactor, and keep the flow rate of sulfate and ammonia constant during the reaction (0.8 L / h). Set the stirring speed to 1000 r / min, and the reaction is carried out at a constant temperature within a temperature range of 55 ° C. Add a precipitant (sodium hydroxide) and a complexing agent (ammonia water) to adjust the pH in the reactor, and keep the pH constant during the reaction at pH 10. After the reaction is completed, the product slurry is centrifuged, washed, filtered, and dried to obtain a precursor of a high-nickel ternary material substrate. The volume average particle size Dv50 of the precursor of the high-nickel ternary material substrate is 10 μm.

[0145] S2: The high nickel ternary material precursor prepared in step S1 is mixed with LiOH·H2O and Y2O3 powder with a molar ratio of 0.002 in a plow mixer, and sintered for the first time to obtain a first lithium nickel cobalt manganese oxide. The total metal molar ratio Li / Me of LiOH·H2O and the high nickel ternary precursor substrate is 1.05, Me is the total molar ratio of Ni, Co, and Mn elements, the first sintering temperature is 720°C, the first sintering time is 15h, and the first sintering atmosphere is O2.

[0146] S3: The first lithium nickel cobalt manganese oxide obtained in step S2 is mixed with Co(OH)2 and subjected to a second sintering, wherein the amount of Co(OH)2 added is such that the mass of the Co element accounts for 12000ppm of the first lithium nickel cobalt manganese oxide, the second sintering temperature is 600°C, the second sintering time is 8h, and the second sintering atmosphere is O2, to obtain a second lithium nickel cobalt manganese oxide, i.e., the surface of the first lithium nickel cobalt manganese oxide is coated with cobalt oxide.

[0147] S4: The second lithium nickel cobalt manganese oxide obtained in step S3 is mixed with B2O3 and sintered for the third time, wherein the amount of B2O3 added is 800ppm of the mass of the B element in the second lithium nickel cobalt manganese oxide, the third sintering temperature is 300°C, the third sintering time is 6h, and the third sintering atmosphere is O2 to obtain a third lithium nickel cobalt manganese oxide.

[0148] In the embodiment of the present application, the third lithium nickel cobalt manganese oxide is used as the positive electrode active material, Li 1.02 Ni 0.918 Co 0.07 Mn 0.01 Y 0.002O2, surface coated with cobalt oxide and boron oxide.

[0149] Preparation method of positive electrode sheet:

[0150] The positive electrode active material, conductive carbon black (Super-P) and polyvinylidene fluoride (PVDF) were mixed with N, N-dimethylpyrrolidone (NMP) at a weight ratio of 96.5:3:1.5, and stirred evenly to obtain the slurry of the positive electrode sheet, and the slurry of the positive electrode sheet was evenly coated on both sides of the aluminum foil. The electrode sheet was cold pressed and sliced ​​to obtain the positive electrode sheet.

[0151] Preparation method of negative electrode sheet:

[0152] In the embodiment of the present application, the negative electrode active material, the conductive agent, the thickener and the binder are mixed with deionized water to form a slurry of the negative electrode sheet. Specifically, in the embodiment of the present application, the negative electrode active material includes a silicon-based material and a carbon-based material. The carbon-based material is artificial graphite, and the silicon-based material is nano-silicon. The conductive agent is conductive carbon black (Super-P) and carbon nanotubes. The thickener is sodium carboxymethyl cellulose (CMC-Na). The binder is styrene-butadiene rubber (SBR).

[0153] Specifically, in the embodiment of the present application, artificial graphite, conductive carbon black (Super-P), carbon nanotubes, sodium carboxymethyl cellulose (CMC-Na), and styrene-butadiene rubber (SBR) are mixed with deionized water in a weight ratio of 96.9:0.5:0.1:1:1.5, and stirred evenly to obtain a slurry for coating the negative electrode sheet. The viscosity can be adjusted by deionized water during the stirring process. Then, the slurry is coated on both sides of the negative electrode collector with a certain width, and the negative electrode sheet is obtained by cold pressing and slicing. In the embodiment of the present application, the negative electrode collector is a 6μm thick copper foil, and the embodiment of the present application does not limit the material and thickness of the negative electrode collector.

[0154] Preparation method of lithium ion secondary battery:

[0155] The positive electrode sheet, the separator and the negative electrode sheet are wound into a battery cell assembly, and a lithium-ion secondary battery is obtained by welding the pole ears, packaging the aluminum shell, injecting liquid, packaging and forming, and vacuum forming. The width of the battery cell assembly is 148mm, the thickness is 28mm, the height is 98mm, and the capacity is 60Ah. Among them, the injected electrolyte is a 1mol / L LiPF6 solution, and the solvent of the LiPF6 solution is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the volume ratio of ethylene carbonate (EC) and dimethyl carbonate (DMC) is 1:2. In the embodiment of the present application, the separator adopts 7μm thick polyethylene (PE).

[0156] The lithium-ion secondary battery obtained in the embodiment of the present application includes a positive electrode sheet and a negative electrode sheet, the positive electrode sheet includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel in all transition metal elements is 91.8%; the positive electrode active material includes secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 650nm. The primary particles include radial primary particles. In the cross-sectional scanning electron microscope image of the secondary particles, the radial primary particles are primary particles whose minimum angle between the long axis direction of the primary particles and the radius direction of the secondary particles is less than or equal to 20°; the secondary particles include radial secondary particles, based on the total number of primary particles in a single radial secondary particle, the number of radial primary particles accounts for 89%; the crushing force of the radial secondary particles is 38mN; the number of radial secondary particles accounts for 95%.

[0157] Embodiment 2-7

[0158] The other differences from Example 1 are detailed in Table 1 and Table 2, and the rest are similar to Example 1.

[0159] Comparative Example 1

[0160] Preparation method of positive electrode active material:

[0161] S1: Prepare the high nickel ternary material substrate precursor by coprecipitation reaction: According to the molar ratio of Ni, Co and Mn elements in the high nickel ternary material substrate of 0.918:0.07:0.01, prepare the sulfate solution of Ni, Co and Mn with a concentration of 5 mol / L, and prepare the NaOH solution with a concentration of 2 mol / L and the ammonia solution with a concentration of 2 mol / L at the same time, add 20% of pure water by volume to the reactor, pump the above three solutions into the reactor, and keep the flow rate of sulfate and ammonia constant (0.8 L / h) during the reaction. Set the stirring speed to 1000 r / min, and the reaction is carried out at a constant temperature within a temperature range of 55 ° C. Add a precipitant (sodium hydroxide) and a complexing agent (ammonia water) to adjust the pH in the reactor, and keep the pH constant during the reaction, pH 11. After the reaction is completed, the product slurry is centrifuged, washed, filtered, and dried to obtain a precursor of a high-nickel ternary material substrate, and the volume average particle size Dv50 of the precursor of the high-nickel ternary material substrate is 10.5 μm. Among them, the concentration of the complexing agent in the coprecipitation reaction is small, the pH value is large, and the concentration of the complexing agent is low. When the pH value is large, the balance of the coprecipitation reaction is more inclined to the nucleation of the precursor material rather than growth. Excessive nucleation results in insufficient time for the primary particles of the material to grow into longer grains, so the primary particles of the precursor obtained are randomly stacked rather than radially grown.

[0162] S2: The high nickel ternary material precursor prepared in step S1 is mixed with LiOH·H2O and Y2O3 powder with a molar ratio of 0.002 in a plow mixer, and sintered for the first time to obtain a first lithium nickel cobalt manganese oxide. The total metal molar ratio Li / Me of LiOH·H2O and the high nickel ternary precursor substrate is 1.05, Me is the total molar amount of Ni, Co, and Mn elements, the first sintering temperature is 750°C, the first sintering time is 16 hours, and the first sintering atmosphere is O2.

[0163] S3: Mix the first lithium nickel cobalt manganese oxide obtained in step S2 with Co(OH)2 and perform a second sintering, wherein the amount of Co(OH)2 added is 12000ppm by mass of Co element based on the first lithium nickel cobalt manganese oxide, the second sintering temperature is 600°C, the second sintering time is 6h, and the second sintering atmosphere is O2, to obtain a second lithium nickel cobalt manganese oxide, i.e., the surface of the first lithium nickel cobalt manganese oxide is coated with cobalt oxide.

[0164] S4: The second lithium nickel cobalt manganese oxide obtained in step S3 is mixed with B2O3 and sintered for the third time, wherein the amount of B2O3 added is 800ppm of the mass of the B element in the second lithium nickel cobalt manganese oxide, the third sintering temperature is 350°C, the third sintering time is 10h, and the third sintering atmosphere is O2 to obtain a third lithium nickel cobalt manganese oxide.

[0165] The lithium ion secondary batteries of Examples 1-10 and Comparative Examples 1-2 were subjected to battery performance tests. The positive electrode active materials were subjected to standard tests.

[0166] (1) The proportion of radial primary particles in radial secondary particles:

[0167] The samples were prepared according to the ion milling scanning electron microscope (CP-EDS) sample preparation standard, and the ion-thinned samples were observed under SEM. A total of 50 secondary particles with a particle size of 6μm to 15μm were photographed, and the proportion of radial primary particles in the 50 secondary particles was counted, and the average proportion of radial primary particles in the 50 secondary particles was taken.

[0168] (2) Crushing force:

[0169] The crushing force test method is to use the Yuanneng Technology single particle mechanical properties test system SPFT1000 for testing, which is mainly composed of an optical microscope, a pressure measurement system, a displacement measurement system, and a force displacement control system. Through high-precision displacement and pressure control, the stress-strain curve after the indenter is loaded on a single particle can be collected, and the particle crushing force can be analyzed from the mutation point of the curve. The test steps include sample preparation, positioning, mode selection and crushing force testing. The displacement loading speed of the flat indenter is 0.1μm / s.

[0170] (3) Test on the proportion of radial secondary particles in secondary particles:

[0171] 50 secondary particles are randomly counted, and the ratio of radial primary particles and Young's modulus are tested. The number of radial secondary particles is counted, and the ratio of radial secondary particles in the secondary particles is obtained by comparing the number of radial secondary particles with 50.

[0172] (4) Average particle size of primary particles:

[0173] The positive electrode active material was tested using a ZEISS sigma 300 scanning electron microscope, and then tested according to the standard JY / T010-1996 to observe the sample morphology.

[0174] Software name: LIBMAS Lithium-ion Battery Material Microscopic Intelligent Analysis System. The scanning electron microscope image of the positive electrode active material is used to automatically identify the single crystal particles by LIBMAS Lithium-ion Battery Material Microscopic Intelligent Analysis System. The particle outline, particle quantity, number, area, maximum caliper diameter, average number, and manual intervention can be drawn. The average particle size of the primary particle = the sum of all measured particle sizes / the sum of all measured primary particle numbers.

[0175] (5) Measurement of the major axis length of primary particles:

[0176] The secondary particles of the positive electrode active material were subjected to ion milling scanning electron microscopy (CP-EDS) testing, cross-sectional scanning electron microscopy images of secondary particles with a particle size of 6 to 15 μm were taken, and the major axis lengths of 50 primary particles were measured.

[0177] (6) Specific surface area test of positive electrode active material:

[0178] The sample to be tested is prepared into a uniform powder or granular form, then placed in a vacuum and set to a specific treatment temperature to remove the gas and moisture adsorbed on the surface. The sample is placed in an adsorption instrument, the liquid nitrogen temperature is set to 77.35K, and the adsorption isotherm is measured by gradually increasing the nitrogen pressure. According to the adsorption isotherm data, the BET equation is used for fitting to obtain the slope and intercept of the adsorption isotherm. According to the parameters in the BET equation, the specific surface area of ​​the sample is calculated.

[0179] (7) Porosity and average pore size test of positive electrode active material cross section:

[0180] The sample powder was adhered to aluminum foil using PVDF and cut under an argon ion beam thinner. The cut section was observed under a scanning electron microscope, and a SEM image of the material cross-section was taken. The pores were identified and the area was calculated using graphics software, and the porosity was then calculated using the ratio of the pore area to the total area.

[0181] The pore size is directly measured using the SEM image. 50 pore sizes are measured and the average value is calculated to obtain the average pore size of the cross section.

[0182] (8) Volume average particle size Dv50, Dv2 test:

[0183] Equipment model: Malvern 2000 (MasterSizer 2000) laser particle size analyzer, reference standard process: GB / T19077-2016 / ISO 13320:2009, specific test process: take an appropriate amount of the sample to be tested (the sample concentration is guaranteed to be 8% to 12% shading), add 20mL of deionized water, and simultaneously ultraviolet for 5min (53KHz / 120W) to ensure that the sample is completely dispersed, and then measure the sample according to GB / T19077-2016 / ISO 13320:2009 standard.

[0184] (9)Dv2 change rate test:

[0185] 1 g of the sample to be tested is placed in a powder compaction mold and pressed with a pressure of 5T for 15 minutes. The pressed powder is then taken out and tested using a laser particle size analyzer to measure the Dv2 value. By comparing it with the Dv2 value before pressing, the Dv2 change rate can be obtained.

[0186] (10) Lithium-ion secondary battery cycle capacity retention test:

[0187] The specific test conditions are: at 25°C, 1 / 3C standard (nominal capacity) constant current charging to a termination voltage of 4.4V, then constant voltage charging to 0.05C standard, set aside for 5 minutes, and then discharge to a discharge cut-off voltage of 2.5V with 1 / 3C standard, and obtain the discharge energy E and capacity C, and the obtained capacity is recorded as the initial capacity C0. Repeat the above steps for the same lithium-ion secondary battery, and record the discharge capacity Cn of the battery after the nth cycle at the same time, then the battery capacity retention rate after each cycle Pn = Cn / C0 × 100%. In this test process, the first cycle corresponds to n = 1, the second cycle corresponds to n = 2, ... the 100th cycle corresponds to n = 100, and the capacity retention rate after 100 cycles is tested.

[0188]

[0189]

[0190] According to the test results in Table 2, compared with the control examples in which the number of radial primary particles accounts for a relatively low proportion, the positive electrode active materials of Examples 1 to 7 provided in the present application exhibit higher crushing force, and the amount of micropowder particles after compression is at a relatively low level, and the corresponding lithium-ion secondary batteries have a higher cycle retention rate. This is because the positive electrode active materials provided in the present application include radial primary particles in a relatively large proportion, and therefore exhibit higher structural stability, thereby improving the cycle performance of the battery.

[0191] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A lithium ion secondary battery, characterized in that: Including positive electrode sheet, negative electrode sheet and electrolyte; The positive electrode plate includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel element in all transition metal elements is greater than or equal to 85% and less than 100%; The positive electrode active material includes secondary particles, the secondary particles include primary particles, the primary particles include radial primary particles, and in a cross-sectional scanning electron microscope image of the secondary particles, the radial primary particles are primary particles whose minimum angle between the long axis direction of the primary particles and the radius direction of the secondary particles is less than or equal to 20°; The secondary particles include radial secondary particles, and based on the total number of the primary particles in a single radial secondary particle, the number of the radial primary particles accounts for 60% to 100%; The crushing force of the radial secondary particles is 2mN to 50mN.

2. The lithium ion secondary battery according to claim 1, characterized in that: The average particle size of the primary particles is 50 nm to 2 μm.

3. The lithium ion secondary battery according to claim 1 or 2, characterized in that: In the positive electrode active material, based on the total number of the secondary particles, the radial secondary particles account for 75% to 95%.

4. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that: In a cross-sectional scanning electron microscope image of the secondary particle, the major axis length of the primary particle is 0.3 μm to 3 μm.

5. The lithium ion secondary battery according to any one of claims 1 to 4, characterized in that: The volume average particle size Dv50 of the positive electrode active material is 6 μm to 15 μm; and / or The volume average particle size Dv2 of the positive electrode active material is 0.5 μm to 4 μm; and / or The specific surface area of ​​the positive electrode active material is 0.2 m 2 / g~1.0m 2 / g; and / or The cross-sectional porosity of the positive electrode active material is 2% to 8%; and / or The cross-sectional average pore diameter of the positive electrode active material ranges from 0.1 μm to 2 μm.

6. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: In the pressure range of 0 to 5 T, the change rate of the volume average particle diameter Dv2 of the positive electrode active material is less than or equal to 20%.

7. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The nickel content of the radial secondary particles from the center to the surface area is equal, or the difference in the nickel content from the center to the surface area is less than or equal to 2%; The manganese content of the radial secondary particles from the center to the surface area is equal, or the difference in the manganese content from the center to the surface area is less than or equal to 0.5%.

8. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that: The positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 e O f material, wherein the M1 element includes one or more of Zr, Ti, Y, Sb, W, Mo, Ba, Ta, Nb, and Al, 0.9≤a≤1.2, 0.85≤b<1, 0.01≤c≤0.09, 0.01≤d≤0.05, 0.001≤e≤0.005, 1.6≤f≤2.4, and b+c+d+e=1.

9. A positive electrode active material, characterized in that: The positive electrode active material comprises lithium nickel cobalt manganese oxide, wherein the molar content of nickel in all transition metal elements is greater than or equal to 85% and less than 100%; The positive electrode active material includes secondary particles, the secondary particles include primary particles, the primary particles include radial primary particles, and in a cross-sectional scanning electron microscope image of the secondary particles, the radial primary particles are primary particles whose minimum angle between the long axis direction of the primary particles and the radius direction of the secondary particles is less than or equal to 20°; The secondary particles include radial secondary particles, and based on the total number of the primary particles in a single radial secondary particle, the number of the radial primary particles accounts for 60% to 100%; The crushing force of the radial secondary particles is 2mN to 50mN.

10. An electrical device, characterized in that: The invention comprises the lithium ion secondary battery according to any one of claims 1 to 8 and / or the positive electrode active material according to claim 9.

Citation Information

Patent Citations

  • Positive electrode material for lithium ion battery with nonaqueous electrolyte, and battery using the same

    CN101167209A

  • Pressure-resistant positive electrode active material and electrochemical energy storage device

    CN111384371A

  • Positive pole piece for secondary battery, secondary battery, battery module, battery pack and device

    CN114556614A

  • Positive pole piece for secondary battery, secondary battery, battery module, battery pack and device

    CN116072816A

  • Positive electrode active material and secondary battery

    CN117691068A

Cited By

  • Positive electrode material, positive plate and battery

    CN120413661A